The Cigarette Marquillas: Graphic Expressions of the Cuban National Identity Formation - Calzadilla Riveira, Yadira (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2020)
The application of lithographic technique during the 19th century in Cuba sparked a large volume of artistic chromolithographies, produced mainly for tobacco commercialization. The first printed in various colors were the «luxury packs» for cigarettes, today known as «cigarette marquillas». In the 1860s, La Honradez factory revolutionized the international cigarette industry through new technologies and commercial strategies, including the use of marquillas. With this, La Honradez set a precedent in cigarette advertising, since the wrappers not only had collectible value, but his picturesque drawings represented Cuban society at the time.